Linkages with Practice for Higher-Education Curriculum Innovation. - Nampala, Paul; Kalule, Stephen W.; Mshenga, Patience M.; Okello, Daniel M.; Egeru, Anthony; Ekwamu, Adipala (Kabale University, 2024)
This article is inspired by the debate on curriculum innovation for graduate training, emerging out of linkages between universities and agribusiness development actors, targeting entrepreneurial action and employability of graduates. Experiences from the implementation of a three-year joint project are enriched by a desk review, stakeholder feedback, and interpretative analysis of process documents during the development of the regional graduate curriculum on Agri-Enterprise Development for Egerton and Gulu Universities in Kenya and Uganda, respectively. The graduate curriculum at the two universities in East Africa integrated the approaches of roundtable engagement and research as well as value chain cluster mapping and development through interactive sharing with agribusiness development facilitators. Simultaneously, the two implementing universities showcased the feasibility of integrating community engagement and entrepreneurial skills into a new curriculum. They achieved this by adopting two training approaches from their previous, more limited curriculum, which lacked student entrepreneurial experiential learning. The outcome from the first cohort of students in the innovative programs demonstrates significant institutional change in teaching and learning approaches. These changes prioritize a blend of action research and theoretical exposure. At the university-wide level, a student-centered teaching and learning approach has been established, facilitated by models like Student Farm Attachment, Student Enterprise Scheme, and Student Community Engagement. Additionally, university-based research teams have honed their skills in community action research, leading to the identification of relevant challenges and plausible solutions. Furthermore, students’ skill sets have increasingly enhanced employability. Strengthening linkages between universities and community development actors can enhance curriculum orientation toward problem-solving and entrepreneurial capacity building for young graduates. Purposeful engagement with communities by university faculty and students serves as a complementary extension approach and advisory service. Implementing an innovative curriculum has the potential to boost research uptake and foster innovation. This article demonstrates how university actors’ collaboration can be exploited for curriculum (re)design, review, and up-dating for (a) enhanced relevance of universities to community needs and employability of graduates; and (b) improvements in the research uptake pathways that facilitate research-into-use for desired impacts at community level.